Desarrollo y validación de una escala de medición para el sistema de gestión de la seguridad laboral - B. Fernández Mu\~niz; J. M. Montes Peón; C. J. Vázquez Ordás (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
Reducing the occupational accident rate and improving competitiveness requires that firms implement an occupational health and safety management system that promotes safe behaviour and workers' personal involvement in activities linked with their well-being at work. The literature has not reached a consensus about the dimensions making up such a system, and few tools have been designed to evaluate this type of management. In this work we review the most relevant literature on the topic, in order to develop and validate a scale for measuring and evaluating preventive management in Spanish companies. For this purpose, we conduct exploratory and confirmatory factor analyses on a sample of 455 firms.
Keywords: 330; safety management system; scale development; psychometric properties; structural equation modelling